Development of blockScholar as an educational mobile application on blockchain technology - Asmawi, Aziah; Saifulbahri, Ezzah Mawadah; Arifin, Noor Afiza Mohd (Semarak Ilmu Publishing, 2024)
In the ever-evolving landscape of technology, blockchain emerges as a transformative force, reshaping digital transactions and decentralized systems. This revolutionary technology, initially synonymous with cryptocurrency, has transcended its roots, becoming a pivotal element in industries spanning finance, supply chain management, healthcare, and more. However, understanding blockchain's intricacies can be daunting, especially for newcomers. This project addresses the need for an accessible and engaging platform to introduce individuals to blockchain technology. Traditional educational resources like textbooks have lost their appeal in today's digital era, leaving learners seeking interactive and mobile-friendly alternatives. While online educational platforms like Udemy and Coursera offer diverse courses, they often lack the immediacy and interactivity that modern learners crave. In the mobile landscape, a noticeable gap exists in educational apps dedicated to blockchain technology. Existing options tend to focus on cryptocurrency, falling short in delivering immersive learning experiences. This project aims to bridge this gap by developing an educational mobile app centered on blockchain technology. The app's primary objective is to offer an interactive and engaging environment for users to explore blockchain's fundamentals, applications, and advantages in a user-friendly manner. By harnessing the ubiquity and convenience of mobile devices, our project seeks to empower learners to delve into the world of blockchain technology. In doing so, we aspire to foster a more informed and tech-savvy community, equipped to comprehend the far-reaching implications of blockchain on various industries. In summary, this project endeavors to unlock the potential of blockchain technology to revolutionize education by creating a mobile app that facilitates the exploration of this transformative field. Through interactive learning experiences and accessible content, we aim to empower individuals to grasp the significance of blockchain and contribute to a more knowledgeable and technologically adept society.